Bearing Capacity of Galam Wooden Foundation on Soft Soil and Peat in Kalimantan Tengah - Silaban, Ridho Saleh (Jurnal Teknik Sipil, 2024)
Many structures in Central Kalimantan are built on soft soil and peat. One type of foundation that can be used for support is the Galam wooden foundation. To ensure stability, the required number of Galam wooden piles must be calculated based on the working load. The foundation"™s bearing capacity is determined through soil testing, such as the Cone Penetration Test (CPT), with the data analyzed using the Meyerhof method. Structural load calculations were performed using SAP2000 software, with the analysis modeled in 3D according to the SNI-1727-2013 loading standard. This study aims to determine the structural load applied to the foundation, the bearing capacity needed for the Galam wooden foundation to support this load, and the required number of wooden piles. The results show that the average foundation load is 11.27 tons for single-story structures, 26.42 tons for two-story structures, and 67.21 tons for three-story structures. A single Galam wooden pile installed at a depth of 0"“8 meters can support a load of 0.82 tons for single-story structures, 1.28 tons for two-story structures, and 2.02 tons for three-story structures. The average number of Galam wooden piles required for group pile foundations is 22 piles for single-story structures, with a load-to-bearing capacity ratio (Pu/Pn) of 0.69; 32 piles for two-story structures, with a ratio of 0.79; and 45 piles for three-story structures, with a ratio of 0.65.